Evaluation of the Blended Learning Program at SD Negeri 1 Baturan Klaten - Chrisdiyanto, Endar; Radite, Ramadian; Hastuti, Sri Retnaning (Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2023)
The Covid-19 pandemic has hampered learning while at the same time making teachers and students learn to carry out online learning. There are obstacles in the implementation of online learning such as the difficulty for teachers to engage active students and decreased student achievement. To overcome this, there is a need for learning innovation by implementing blended learning. The blended learning program is a learning model that combines face-to-face learning with online learning. The purpose of this study was to evaluate the blended learning program at SD N 1 Baturan and to find out the supporting and inhibiting factors in implementing blended learning. The method used in this research is a case study with a qualitative approach. Data collection techniques are carried out by observation, interviews, and documentation. The results of the evaluation show that the blended learning program at SD N 1 Baturan has been implemented well even though it has several obstacles and there are several supporting and inhibiting factors for the blended learning program. Supporting factors include the school environment, government, and teaching staff, while inhibiting factors include facilities and infrastructure, students' technological literacy, and face-to-face time limitations.